2004
DOI: 10.1645/ge-3222
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Characterization of Iron-Containing Superoxide Dismutase From Neospora Caninum

Abstract: A gene encoding superoxide dismutase (SOD) from Neospora caninum, a causative agent of neosporosis, has been cloned and its gene product functionally expressed and characterized. The gene had an open reading frame of 606 bp and deduced 201 amino acids. Sequence analysis showed that the gene had conserved metal-binding residues and conserved amino acid residues that were found in Fe-SODs. Comparison of the deduced amino acid sequence of the enzyme with previously reported Fe-SOD amino acid sequences of the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
3
0
2
Order By: Relevance
“…The molecular mass of the active rCp-mtSOD was determined to be about 50 kDa by gel filtration (data not shown), indicating that the enzyme forms a homodimer as do other classes of Fe-SODs. The rCp-mtSOD showed similar biochemical properties to those of Fe-SODs from other protozoa parasites (Bécuwe et al 1996;Choi et al 2000;Odberg-Ferragut et al 2000;Ahmed et al 2003;Cho et al 2004). The enzyme showed optimum activity for a broad pH range of 7.0 to 9.5, and maximum level of activity was at pH 8.0 (Fig.…”
Section: Molecular Characterization Of Cp-mtsodmentioning
confidence: 69%
See 1 more Smart Citation
“…The molecular mass of the active rCp-mtSOD was determined to be about 50 kDa by gel filtration (data not shown), indicating that the enzyme forms a homodimer as do other classes of Fe-SODs. The rCp-mtSOD showed similar biochemical properties to those of Fe-SODs from other protozoa parasites (Bécuwe et al 1996;Choi et al 2000;Odberg-Ferragut et al 2000;Ahmed et al 2003;Cho et al 2004). The enzyme showed optimum activity for a broad pH range of 7.0 to 9.5, and maximum level of activity was at pH 8.0 (Fig.…”
Section: Molecular Characterization Of Cp-mtsodmentioning
confidence: 69%
“…Superoxide dismutases (SODs; 1.15.1.1) are ubiquitous metalloenzymes that detoxify the highly reactive superoxide anions to hydrogen peroxide and molecular oxygen (Fridovich 1986). SODs have been identified and characterized in various parasitic protozoa and are considered as essential enzymes that protect parasites from endogenous oxidative stress, as well as oxidative killing by host immune effector cells (Bécuwe et al 1996;OdbergFerragut et al 2000;Cho et al 2004;Dufernez et al 2006). The most important feature of protozoan parasite SODs is that they belong to iron-containing SODs (FeSODs), which are not found in their mammalian hosts.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, an SOD enzyme showed higher abundance in the bradyzoite stage. This protein has been detected in both T. gondii (Odberg-Ferragut et al 2000) and N. caninum (Cho et al 2004) bradyzoites and tachyzoites, suggesting that SOD might be essential for the intracellular growth of different developmental stages, protecting the parasite from oxidative killing (Michalski and Prowse, 1991). The higher abundance of SOD in bradyzoites might be explained by the origin of parasite stages because the bradyzoites originated from an in vivo infection, whereas tachyzoites were propagated in an epithelial monkey-derived cell line.…”
Section: Resultsmentioning
confidence: 99%
“…O sistema redox de parasitas Apicomplexas tem sido amplamente estudado em Plasmodium e T. gondii, nos quais já foram descritas diversas moléculas e enzimas antioxidantes, como por exemplo: peroxirredoxinas (AKERMAN; MÜLLER, 2003;BOUCHER et al, 2006), tiorredoxina redutase (MCCARTY et al, 2015;XUE et al, 2017), tioredoxina (JORTZIK;BECKER, 2012;BIDDAU et al, 2018) e glutationa redutase (SARMA et al, 2003;HASSAN et al, 2014). Em Neospora caninum, porém, apenas as enzimas SOD1 e Glutarredoxina 1 (CHO et al, 2004a;SONG et al, 2020) haviam sido descritas antes do presente trabalho, existindo ainda uma ampla gama de moléculas antioxidantes a serem investigadas nesse parasita. Evidências de estudos em Plasmodium e T. gondii e N. caninum mostram que o balanço entre defesas antioxidantes e o estresse oxidativo influenciam diretamente na infecção do organismo hospedeiro.…”
Section: O Controle Redox Em Parasitas Apicomplexasunclassified
“…Ademais, já foi demonstrado que a replicação de N. caninum pode ser inibida através de mecanismos ativados por EROs (MOTA et al, 2020;PEREIRA et al, 2020). No organismo hospedeiro o estudo do estresse oxidativo é embasado em um corpo de evidências de longa data e grande parte de seus componentes são profundamente conhecidos (NORDBERG; ARNÉR, 2001;SORDILLO;AITKEN, 2009), por outro lado, quando olhamos para N. caninum, apenas poucas características de seu sistema redox são conhecidas tanto das proteínas envolvidas como do comportamento frente ao estresse oxidativo (CHO et al, 2004a;MOTA et al, 2020;PEREIRA et al, 2020;SONG et al, 2020. Assim, para contribuir com o entendimento do controle redox em N. caninum e buscar novos alvos de tratamento e vacinas, buscamos descrever duas enzimas conservadas do sistema redox e avaliar o comportamento do parasita frente ao estresse oxidativo.…”
Section: Discussão Finalunclassified